Coherent X‐ray beam metrology using 2D high‐resolution Fresnel‐diffraction analysis. (1st December 2016) - Ruiz-Lopez, M.; Faenov, A.; Pikuz, T.; Ozaki, N.; Mitrofanov, A.; Albertazzi, B.; Hartley, N.; Matsuoka, T.; Ochante, Y.; Tange, Y.; Yabuuchi, T.; Habara, T.; et al.
Abstract : Online metrology of beamline specifications is important but often sacrificed for reasons of time constraints. A technique that permits a reliable metrology without interruption of the measurement workflow is presented. Abstract : Direct metrology of coherent short‐wavelength beamlines is important for obtaining operational beam characteristics at the experimental site. However, since beam‐time limitation imposes fast metrology procedures, a multi‐parametric metrology from as low as a single shot is desirable. Here a two‐dimensional (2D) procedure based on high‐resolution Fresnel diffraction analysis is discussed and applied, which allowed an efficient and detailed beamline characterization at the SACLA XFEL. So far, the potential of Fresnel diffraction for beamline metrology has not been fully exploited because its high‐frequency fringes could be only partly resolved with ordinary pixel‐limited detectors. Using the high‐spatial‐frequency imaging capability of an irradiated LiF crystal, 2D information of the coherence degree, beam divergence and beam quality factor M 2 were retrieved from simple diffraction patterns. The developed beam metrology was validated with a laboratory reference laser, and then successfully applied at a beamline facility, in agreement with the source specifications.